Rethinking Halal: Exploring the Complexity of Halal Certification and its Socio-Economic Implications - Suud Sarim Karimullah; Rozi (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2023)
Halal certification has become a major highlight on the global stage, especially in line with the rapid growth of the halal product market. This study aims to thoroughly review the concept of halal and explore its important implications in the social and economic spheres, as well as challenges and opportunities in halal certification. This study is a literature study conducted with a comprehensive literature analysis approach. This literature analysis includes the process of Investigation, data collection, and in-depth analysis of various literature sources that are relevant to the subject of study. The results of this study highlight that halal certification is a complex and diverse process with significant social and economic impacts. The different certification processes in other countries and organizations pose substantial challenges in global trade but also open up great opportunities in the halal product market. In the social dimension, halal certification plays an important role in maintaining Muslim communities' religious beliefs and values but also poses a risk of discrimination against non-Muslim communities in this economic sphere. The main challenges that need to be addressed include harmonizing global standards and preventing abuse in the halal certification process. Meanwhile, the economic opportunities associated with halal products remain large, particularly in line with the growing global demand.